Syntactic Theory Perception on Language Acquisition - Zaghwani Omar, Dr.Youssif (مجلة كلية الاداب, 2022)
This paper focuses on identifying the syntactic theory perception on acquiring first language. The paper highlights the role and function of language syntactic structure in childhood on acquiring first language from birth and using it in communicative situations in reality later. The paper, however, emphasizes the impact of grammatical development, focusing mainly on nativist and usage-based, on acquiring first language. The paper bases its hypotheses and assumptions on Chomsky’s universal grammar and transformation grammar theories. The study, moreover, exposes language as a symbolic system and how it is formed in mind from birth, focusing mainly on the difference between human language and animal sounds. A brief idea about linguistic and communicative competence is presented to associate them to first language acquisition. the study concludes that grammar, which is part of the syntactic theory, is concerned with discovering the principles and sets of rules used for governing the structures of utterances and sentences. These principles and sets of rules constitute what is called linguistic competence of language. This linguistic competence is what helps children acquire their first language.